Peningkatan Komitmen Profesi Guru Melalui Kepemimpinan Transformasional Kepala Sekolah, Budaya Organisasi, Dan Motivasi Berprestasi - Sukoco, Hadi; Hidayat, Rais; Muharam, Hari (Universitas Pakuan, 2024)
IMPROVING TEACHERS' PROFESSIONAL COMMITMENT THROUGH PRINCIPALS' TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND ACHIEVEMENT MOTIVATIONThis research aims to find effective and efficient ways to increase teachers' professional commitment by examining the influence of variables that are thought to have a relationship with teachers' professional commitment. These variables are Transformational Leadership and Organizational Culture. and Achievement Motivation. The methods found are then used as input and recommendations to teachers, school principals, management or foundations, school supervisors, and the education department. This research also attempts to identify indicators of research variables that need to be improved and those that need to be maintained. This research uses a survey method with path analysis techniques (Path Analysis). The population in this study was 358 Permanent Foundation Teachers in 46 Private Middle Schools in Pancoran Mas District, Depok City. The sampling technique in this research used a proportional random sampling technique using the Slovin formula with an error margin of 5%. The number of samples used in this research was 189 GTY respondents in private junior high schools in Depok City District. The research results show a positive direct influence of transformational leadership on teachers' professional commitment through achievement motivation and a positive direct influence of organizational culture on teachers' professional commitment through achievement motivation.